Lessepsian fishes at the bottom trawl fishery in the Babadillimani bigth, northeastern mediterranean coast of Turkey - E. Çiçek; D. Avsar (ՀՀ ԳԱԱ հրատ.)
Предложена математическая модель поведения астроцита при различных условиях кальциевых колебаний постсинаптического нейрона. Разработанная модель астроцита может использоваться для исследования долгодлящейся синаптической пластичности в трипартитном синапсе (ТПС). Առաջադրված է աստրոցիտի վարքագծի մաթեմատիկական մոդել պոստսինապտիկ նեյրոնի կալցիումի տատանումների տարբեր պայմաններում: Աստրոցիտի մոդելը կարող է օգտագործվել եռմասանի սինապսում երկարատև սինապտիկ ճկունության ուսումնասիրման ժամանակ:A mathematical model of the behavior of astrocyte in different conditions of calcium oscillations of postsynaptic neuron was proposed. The developed model of astrocyte can be used to study the long synaptic plasticity in tripartite synapse.
Keywords: Agriculture; Aquaculture; Fisheries; Angling; Biology